A review of the species of Lithostege Hübner, [1825] 1816 (Lepidoptera: Geometridae, Larentiinae), occurring in Iran and adjacent countries, with description of two new species from Iran and Pakistan - Sh., Hossein Rajaei; Stüning, Dieter; Viidalepp, Jaan (Zootaxa, 2011)
The Iranian species of Lithostege are reviewed and additional species from neighbouring countries (which are also likely to occur in Iran), as a whole twenty-eight taxa, are studied. Adults of all species and male and/or female genitalia for most species are figured. Two new species are described: L. samandooki Rajaei sp. nov. from Iran and L. hreblayi Rajaei & Viidalepp sp. nov. from Pakistan. L. repeteki Tsvetajev and L. griseata gigantea Bytinski-Salz & Brandt are synonymized with L. obliquata Urbahn and L. griseata griseata (Denis & Schiffermüller), respectively. L. amseli Wiltshire is discussed as a possible synonym of L. amoenata Christoph. L. flavicornata (Zeller) is upgraded to species-rank again. Distribution areas of all species discussed are shown by maps. Literature data concerning faunistics, ecology, and biological data are reviewed. Female genitalia of L. obliquata Urbahn, L. turkmenica Tsvetajev, and L. luminosata Christoph, are figured and their morphological characters compared with other taxa for the first time. A check list is presented and a preliminary grouping of species treated is proposed, based largely on morphological characters of the genitalia. It does not necessarily reflect a natural relationship of the species included, but may provide a first structure to the genus, as a basis for future studies.